2020
DOI: 10.1590/s1984-29612019110
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites of household and shelter cats in the city of Rio de Janeiro, Brazil

Abstract: Endoparasitic infections are associated with morbidity in cats. This study aimed to investigate the occurrence of endoparasites among cats of different life stages in the city of Rio de Janeiro, Brazil. The samples were analyzed individually by macroscopic exploration for proglottids and centrifugal-flotation. Stool samples were obtained from household cats (n = 57) and shelter cats (n = 336). Endoparasites were detected in 50.64% of the samples. Among household and shelter cats, 21.05% and 55.66% were infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
3
5
0
1
Order By: Relevance
“…Hookworms were the second most prevalent parasites in this study (22.2%), which is similar to published data [30,31]. Infection of cats with hookworms may occur via ingestion of free larvae from the soil or paratenic hosts, maternal milk and transcutaneous penetration by infective larvae.…”
Section: Discussionsupporting
confidence: 91%
“…Hookworms were the second most prevalent parasites in this study (22.2%), which is similar to published data [30,31]. Infection of cats with hookworms may occur via ingestion of free larvae from the soil or paratenic hosts, maternal milk and transcutaneous penetration by infective larvae.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to our data Capari et al (2013) study found that the prevalence of endoparasites infection in Hungarian domestic cats was 17.4%. The data is comparable with studies from Brazil and Cyprus where T. cati was found to be prevalent in 16.67% and 12%, respectively (Diakou et al, 2017;Ramos et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Parasites with zoonotic potential, such as Toxocara sp., hookworms, Dypilidium caninum, Giardia duodenalis, Cryptosporidium spp. and Toxoplasma gondii, stand out among the ones identified in these animals (Arruda et al, 2021a, b;Balassiano et al, 2009;Bastos et al, 2014;Cunha et al, 2016;Leal et al, 2015;Ramos et al, 2020). Owners' lack of knowledge about parasites may be one of the factors contributing to animal infections and to parasites' permanence in the environment.…”
Section: Introductionmentioning
confidence: 99%